EFL Students’ Perception Toward Online Classes - Muhammad Hasby; Edi Wahyono; Ardhy Supraba (Universitas Cokroaminoto Palopo, 2021)
The previous year at Cokroaminoto Palopo University widely used a number of online learning platforms such as google meet, google classroom, zoom, whatsapp, learning management system and others, this beared a shock therapy for all students, lecturers and even employees, where they should start doing such work and learning activities, which were initially carried out directly on campus, became predominantly carried out online and mostly from homes. This research is a qualitative descriptive study using semi-structured interviews, it is conducted with a number of students majoring in English education who are under the teaching faculty and education science at Cokroaminoto University Palopo. After the study was conducted, it was concluded that these students felt the both positive and negative sides of online learning, the positive side was that they did not need to go to campus to do classroom learning, this is t can save time and accommodation, on the other hand they sometimes experience difficulties either because of the limited internet access, or the availability of the internet network where the student is located, then spending more budget in the form of internet and it has increased significantly for all students, especially on the zoom application.